The neurocognitive processing mechanism of English subject-verb agreement by Chinese-speaking learners - Wu, Mingjun; Li, Miaomiao; Wu, Di (Frontiers in Psychology, 2024)
Determiner phrases (DP), an overarching term, can be classified into two determiner types, referential determiner phrases (RDP, e.g., the boy) and quantificational determiner phrases (QDP, e.g., each boy). Using the event-related potential (ERP) technique, this study explored the modulation of RDP vs. QDP in the online processing of English subject-verb agreement with omission errors by Chinese learners of English, addressing the question of whether singular quantification increases or decreases Chinese learners' sensitivity to agreement violations. The experiment manipulated the determiner type, specifically RDP vs. QDP, and grammaticality (grammatical vs. ungrammatical). The results indicated that similar to previous studies, a P600 effect was elicited in response to subject-verb agreement violations with omission errors, demonstrating that Chinese L2 learners are sensitive to such agreement violations. Additionally, the ERP patterns exhibited variations due to D-linking and number specification of RDP and QDP. Regarding D-linking, subject-verb agreement violations in the QDP conditions, necessitating integration of discourse-related knowledge, elicited laterally and frontally distributed P600 effects associated with integration complexity at the discourse level; however, non-D-linked referential determiners elicited the posteriorly-distributed P600 effects. Differences in number specification resulted in the distinctive P600 latencies and whether P600 was preceded by N400 or not. While both the RDP and QDP conditions exhibited the P600 effects, the onset latency of this effect in the number-unspecified RDP condition was 300ms later compared to the number-specified QDP condition. Furthermore, an additional N400 component observed in the RDP condition suggests that L2 learners acquire morphologically complex subject-verb agreements by rote, treating them as unanalyzed chunks. This N400 component was absent in the QDP condition. From these results the conclusion can be drawn that L2 learners are sensitive to subject-verb agreement violations with omission errors and L2 processing patterns of subject-verb agreement varies with different features of determiners, providing further evidence for the cuebased retrieval model during comprehension of grammatical sentences. Pedagogical implications are provided and the future research direction is suggested.